PENGARUH TINGKAT KECERDASAN ADVERSITAS DAN SIKAP BELAJAR MANDIRI SISWA TERHADAP PRESTASI BELAJAR IPS SISWA KELAS 6 SEKOLAH DASAR DI KECAMATAN NALUMSARI KABUPATEN JEPARA - Noor Avni (COLLASE (Creative of Learning Students Elementary Education), 2023)
This study aims to analyze the effect of analyzing the level of adversity intelligence and students' independent learning attitudes on social studies learning achievement of 6th grade elementary school students in Nalumsari District, Jepara Regency. The object of the research includes three elementary schools, namely SDN Jatisari, SDN 1 Gemiring Lor, and SDN 2 Gemiring Kidul. Data collection techniques using a questionnaire. Data analysis technique with regression analysis with SPSS. The results showed that partially adversity intelligence variable had a significant positive effect on students' social studies learning achievement. Likewise, the development of the independent learning attitude variable has a significant positive effect on students' social studies learning achievement. The results of multiple linear regression show that the adversity intelligence variable and the independent learning variable simultaneously have a significant positive effect on the social studies learning achievement of 6th grade public elementary school students in Nalumsari District, Jepara in the even semester of the 2021/2022 academic year.